Robot-assisted primary cementless total hip arthroplasty with a short femoral stem: a prospective randomized short-term outcome study. (2nd January 2015) - Lim, Seung-Jae; Ko, Kyung-Rae; Park, Chan-Woo; Moon, Young-Wan; Park, Youn-Soo
Abstract: Background : Recently, two topical issues in total hip arthroplasty (THA) have been robot-assisted surgery and use of a short stem. The purpose of this study was to evaluate the effects of robotic milling on the accuracy of short femoral stem positioning and on the short-term clinical outcome in THA using a prospective, randomized design. Methods : We randomized 54 patients into two groups, either robotic milling group or manual rasping group. The patients were assessed clinically and radiographically at 8 weeks, 5 months, 12 months, and 24 months. Results : Robotic milling group had a significantly longer operation time, requiring on average 8.9 min for registration and 11.2 min for milling. On the other hand, robotic milling group showed superior results in terms of stem alignment and leg length equality. Two intraoperative femoral fractures occurred only in manual rasping group. Harris hip scores and WOMAC scores at 24 months postoperatively were similar in both groups. No complications including stem loosening, infection, nerve palsy, or dislocation were encountered in either group during the follow-up period. Conclusions : The present study suggested that robot-assisted short stem THA could increase the accuracy of stem alignment, improve leg length equality, and help reduce the risk of intraoperative femoral fracture as compared with manual rasping. However, the clinical outcome scores did not differ between the two groups at the time of short-term follow-up. Long-term follow-up is needed to determine whether there will be a long-term clinical relevance of robot-assisted implantation of short femoral stems in THA.